The Effectiveness of using High Protein Products in the Context of Muscle Mass Gain: A review of the Literature - Markiewicz, Agnieszka Ewelina; Molenda, Marek Jarosław; Wachowska, Maria; Szymura, Marta; Paniak, Mateusz; Romaniuk, Mateusz; Krawczyk, Michał Brunon; Woszczyńska, Oliwia Brygida; Rycąbel, Paweł Maciej; Sowiński, Wojciech (Quality in Sport, 2025)
Introduction: High-protein food is widely recommended in sports dietetics as a key component to support muscle hypertrophy. More products with higher amounts of protein in the ingredients are being introduced to the market. Among the products that are available there are both animal and plant-based products, including dietary supplements, fermented milk drinks, protein bars and other high-protein snacks. The diversity of forms, flavour profiles and nutritional composition of these products allows them to be customised to meet individual dietary needs, consumer preferences and varying dietary patterns. Materials and Methods: This article presents a review of scientific studies from the years 2015-2025 available in the PubMed database on the effectiveness of protein supplementation for muscle mass gain in physically active individuals and athletes. Research Objective: The aim of this review is to bring together the current knowledge on the role of higher protein intake and supplementation in the diet. Particular attention is paid to the quantity and quality of protein intake, types of supplements, biochemical mechanisms determining hypertrophy and potential side effects of excessive protein supply. Results and Conclusions: Protein supplementation combined with customized physical activity is needed to accelerate muscle tissue growth. Further research on protein supplementation is needed, as current findings do not yet allow definitive conclusions.